Visual speech in media: case of manipulation - Gabriela Noemi Garcia Tamayo; Gurieva, N. (ХНУРЕ, 2022)
The aim of the following investigation is to show how visual discourse can be exploited in digital communication. Especially how visual communication can be taken advantage of when practicing soft power and creating an appealing or dramatic image of the event described in the news. The image is equal to or more powerful than a striking headline and at a perceptual level, that’s why the image can abbreviate extensive content and encrypt the news itself.
Keywords: media; manipulation